PC-Asymptotically almost automorphic mild solutions for impulsive integro-differential equations with nonlocal conditions - IKHLEF, Nadia; BENSALEM, Abdelhamid; SALIM, Abdelkrim; BENCHOHRA, Mouffak; LITIMEIN, Sara (Studia Universitatis Babeș-Bolyai Mathematica, 2025)
In this article, we study the existence of PC-asymptotically almost automorphic mild solutions of integro-differential equations with nonlocal conditions via resolvent operators in Banach space. Further, we give sufficient conditions for the solutions to depend continuously on the initial condition. Finally, an example is given to validate the theory part. Mathematics Subject Classification (2010): 47H10, 45J05, 47H08, 35D30, 47B40. Received 21 July 2023; Accepted 04 September 2023.